Cover Feature: Theoretical Study on Open‐Shell Singlet Character and Second Hyperpolarizabilities in Cofacial π‐Stacked Dimers Composed of Weak Open‐Shell Antiaromatic Porphyrins (ChemPhysChem 21/2018). Issue 21 (11th October 2018) - Fujiyoshi, Jun‐Ya; Tonami, Takayoshi; Yamane, Masaki; Okada, Kenji; Kishi, Ryohei; Muhammad, Shabbir; Al‐Sehemi, Abdullah G.; Nozawa, Ryo; Shinokubo, Hiroshi; Nakano, Masayoshi
Abstract : The Cover Feature shows a proposal of a novel promising strategy for enhancing third‐order nonlinear optical (NLO) property along the stacking direction of weak open‐shell antiaromatic porphyrin dimers through the enhancement of open‐shell characters originating in the cofacial π‐stacking interactions between the antiaromatic molecules. More information can be found in the Article by J.‐Y. Fujiyoshi et al. onpage 2863 in Issue 21, 2018 (DOI:10.1002/cphc.201800745 ).